EKSPLORASI MIKROORGANISME INDIGENUSINSEPTISOLS - Nurmala Pangaribuan (Jurnal Matematika Sains dan Teknologi, 2018)
Inseptisols have various types and densities of microorganisms. Plants that are cultivated in Jatinangor inseptisol fields have a root system that contains a large number of microorganisms. This study aims to be able to provide precise information about the potential resources of microorganisms, bacteria, mycorrhizae from the location of planting corn and soybeans on Jatinangor and Ciparanje inseptisols, Sumedang, West Java. This research activity includes (1) soil sampling which was then isolated on oblique agar media observed with a microscope, (2) identification of spore types, identification of CMA using the Manual for The Identification of Mychorhiza Fungi, (3) calculating the number of spores using the Filter Method Wet Pacioni and Centrifugation Technique from Brunndret. The results showed the number of Bradyrhizobium sp.,was found in the former soil of soybean cropping in Jatinangor and Ciparanje, which was 7,75 x 108 cfu/g, higher than in the former corn crop, 1,80 x 107 cfu / g in Jatinagor and 1,41 x 107 cfu /g at Ciparanje. Inseptisols Jatinangor and Ciparanje also produce spores of Glomus sp. 14 spores /g of soil and 12 spores/g of soil, in the former maize cropland were higher than in the former soybean cropland, which was 10 spores/g of soil. Ekosistem inseptisols memiliki jenis dan kepadatan mikroorganisme yang beragam. Tanaman yang dibudidayakan di lahan inseptisol Jatinangor memiliki sistem perakaran yang mengandung berbagai jenis mikroorganisme dalam jumlah besar. Penelitian ini bertujuan untuk dapat memberikan informasi yang tepat tentang potensi sumberdaya mikroorganisme, bakteri, mikoriza dari lokasi penanaman jagung dan kedelai padalahan inseptisol Jatinangor dan Ciparanje, Sumedang, Jawa Barat. Kegiatan penelitian ini meliputi (1) pengambilan sampel tanah yang kemudian diisolasi pada media agar miring yang diamati dengan mikroskop, (2) identifikasi jenis spora, identifikasi CMA menggunakan Manual for The Identification of Mychorhiza Fungi, (3) penghitungan jumlah spora dengan menggunakan Metode Saring Basah Pacionidan Teknik Sentrifugasi dari Brunndret. Hasil penelitian menunjukkan jumlah bakteri Bradyrhizobium sp. Lebih banyak ditemukan pada tanah bekas pertanaman kedelai di Jatinangor dan Ciparanje, yaitu 7,75 x 108 cfu/g, sementara pada bekas pertanaman jagung, di Jatinangor 1,80 x 107 cfu/g dan 1,41 x 107 cfu/g di Ciparanje. Inseptisols Jatinangor dan Ciparanje mengandung Glomus sp., di Jatinangor dan Ciparanje berturut-turut 14 spora/g tanah dan 12 spora/g tanah, lebih tinggi pada tanah bekas pertanaman jagung, dibanding pada tanah bekas pertanaman kedelai, yaitu 10 spora/g tanah.